ECOLOGY OF DIGITAL ATTENTION AND STUDENT SELF-REGULATION: A CONCEPTUAL ANALYSIS OF CHARACTER EDUCATION IN THE PLATFORM ERA - Putra Asga Elevri; Yadi Ruyadi; Encep Syarief Nurdin; Asep Dahliyana (SOSIOEDUKASI, 2026)
The development of digital platforms has helped to reshape the learning, communication, entertainment, and social relations environment of adolescent students. In this context, digital attention is more proportionate to be understood not only through screen duration or device use settings, but also through media usage habits, social-pedagogical relationships, norms of technology use, and platform design and incentives as part of the student's digital environment. This article aims to compile a conceptual analysis of the relationship between the ecology of digital attention, adolescent self-regulation, and character education in the platform era. Using a conceptual study based on directed narrative literature, this article proposes "the ecology of digital attention" as a conceptual working term and an analytical construct for reading students' attention relationally in a digital environment. Conceptually, digital self-regulation can be understood as a capacity of relational character that includes: 1) goal setting; 2) impulse management; 3) attention management; 4) monitoring of digital habits; 5) reflection on consequences, and 6) digital responsibility. In this position, character education can provide space for reflection on digital use, responsible habituation, attention management, and the development of practical wisdom in students' digital lives. This article is not intended to test empirical relationships, evaluate policies, or assess specific programs.